Extremely selective detection of ppb levels of indoor xylene using CoCr2O4 hollow spheres activated by Pt doping. Issue 6 (6th December 2018) - Lee, Kun Ho; Kim, Bo-Young; Yoon, Ji-Wook; Lee, Jong-Heun
Abstract : Ultrasensitive and extremely selective detection of indoor xylene is achieved by using Pt-doped CoCr2 O4 hollow spheres. Abstract : Ultrahigh gas selectivity and response for ppb levels of xylene are achieved by doping Pt in CoCr2 O4 hollow spheres, whereas the addition of Au or Pd is less effective or even deteriorated the performance.